Strengthening the Rule of Law in the EU: The Council's Inaction*. (21st July 2016) - Oliver, Peter; Stefanelli, Justine
Abstract: In May 2014 the Legal Service of the Council delivered an opinion on the European Commission's Rule of Law Framework, stating the Commission's new mechanism was unlawful. This article sets out a critical analysis of this opinion, and questions whether the annual rule of law dialogue announced by the Council in December 2014 is a feasible response. Hungary is used as a case study to highlight the total failure of the Council to take any action whatsoever in the face of the grave and systemic abuses of human rights committed by the government of that country since 2010; and Poland where an autocratic regime has been in place since the autumn of 2015 is also mentioned. This is contrasted with the efforts of the majority of the Members of the European Parliament to tackle the acute challenge and with the Commission's action on specific breaches. A co‐ordinated strategy is sorely needed. Abstract : This article is part of the September 2016 Symposium titled 'The Great Rule of Law Debate in the EU', which also includes The Great Rule of Law Debate in the EU by Dimitry Kochenov, Amichai Magen and Laurent Pech (DOI:10.1111/jcms.12399 ), Cracks in the Foundations: Understanding the Great Rule of Law Debate in the EU by Amichai Magen (DOI:10.1111/jcms.12400 ), Better Late than Never? On the European Commission's Rule of Law Framework and its First Activation by Dimitry Kochenov and Laurent Pech (DOI:10.1111/jcms.12401 ), The European Parliament's Role: Towards New Copenhagen Criteria for Existing Member States? by Judith Sargentini and Aleksejs Dimitrovs (DOI:10.1111/jcms.12403 ), Upholding Shared Values in the EU: What Role for the EU Agency for Fundamental Rights? by Gabriel N. Toggenburg and Jonas Grimheden (DOI:10.1111/jcms.12404 )